La capacità di agency tra essere umani e sistemi di intelligenza artificiale questioni antropo-etiche - Caltagirone, Calogero (Antonianum, 2025)
An analysis is offered here of the impact of artificial inteligence on the forms of human acting and on the redefinition of subjectivity, within a context, in which human beings now live immersed in an informational and digital ecosystem that generates new processes of anthropological change. The current techno-human condition requires an epistemological, ontological, and anthropological rethinking of "agency", since acting becomes an informational "inter-term" within the relational interactions between the human and the artificial. The need is highlighted here of understanding how machines may be able to acquire some form of autonomous agency - albeit one different from that of human beings - as a "producing of effects" grounded in algorithmic procedures. From this arises the urgency of a "fundamental anthropo-ethics" to give direction to human well-being in the infosphere and to define ethical criteria and responsabilities for AI while avoiding any limitation of the normative to the statutory. The novelty of this approach lies in proposing a relational and informational view of agency, shared and distributed between human beings and artificial systems, geared to acknowledging the latter as moral agents, in a renewed metaethical perspective.